Genetic Diversity Analysis of 41 Chili Pepper Genotypes (Capsicum annuum L.) Based on SSR Markers - Wartono Wartono; Suryo Wiyono; Muhamad Syukur; Giyanto Giyanto; Kristianto Nugroho; Puji Lestari (Jurnal AgroBiogen, 2019)
Chili (Capsicum annuum L.) is an important horticultural crop which possesses high genetic diversity. Their genetic diversity needs to be assessed through molecular marker-based analysis to facilitate chili breeding scheme. The objective of the study was to analyze the genetic diversity of 41 chili genotypes using Simple Sequence Repeat (SSR) markers. Eleven SSR markers were used to amplify all genotypes through PCR technique, visualized on Polyacrylamide Gel Electrophoresis (PAGE). The data were analyzed using NTSYSpc version 2.1 and PowerMarker version 3.25 softwares. Results showed that the average of SSR alleles was 7.9 with a range of 4-11 alleles per marker. All SSR markers showed PIC value >0.5, indicating their suitable use for chili genetic studies. Cluster analysis of 41 genotypes generated three main groups according to coefficient similarity of 77.4%. The genetic clusters appeared as reflection of the genetic background of each genotype. In addition, the SSR markers used can identify potential parent as indicated by the genetic distance between genotypes. The highest genetic diversity (0.698) was demonstrated by combinations of Yuni × Ayesha, Yuni × Ayesha 2, and Yuni × Namira. The estimated genetic diversity produced by SSR markers in this study should be useful as guidance for chili breeders to select suitable parents for new cultivar development for high productivity and resistance to diseases.